Design of Lightning Strike Hazard Zone Detection System for Direct Lightning Strike Prevention in Open Area - Nugraha, Adi; Al Bantani, Rahmat Ato'ullah Gumilang; Grahito; Yudono, Muchtar Ali Setyo; Suryana, Anang (Fidelity : Jurnal Teknik Elektro, 2024)
Lightning is a dangerous natural phenomenon due to its high-voltage electrical energy, which can cause significant damage. The primary hazard of lightning is direct strikes, potentially leading to severe burns, organ failure, and even death. Additionally, lightning can trigger fires, disrupt power grids, and cause explosions. To mitigate these risks, this research focuses on designing a lightning detection system using the "rolling sphere" method. The lightning strike zone is modeled using CorelDRAW software, aiding users in visualizing areas prone to lightning strikes. The device is assembled with electronic components designed to detect lightning based on the method, considering parameters such as peak current, current steepness, charge, and impulse force. Once assembled, the system undergoes testing in an open area at the Faculty of Engineering, Sultan Ageng Tirtayasa University, to verify its functionality and accuracy. Testing is conducted at night to minimize weather-related disturbances, such as Cumulonimbus clouds. The results confirm that the device operates as expected, successfully identifying areas at risk of lightning strikes. This system is anticipated to enhance safety and infrastructure protection in lightning-prone regions.